(untitled) (Marketing Journal, 2025)
This article examines the development trends of e -commerce in Uzbekistan. It analyzes the growth dynamics observed in the e -commerce sector, key influencing factors, and the support measures provided by the government. Additionally, it provides insights in to Uzbekistanʼs e -commerce infrastructure and major platforms. The study explores the impact of e -commerce on economic growth based on real data and statistical analysis.